Breaking Down the Silos Between the Introductory Financial Accounting and Corporate Finance Courses - Schatzel, John; Ciamarra, Elif Sisli; Yen, Alex (Journal of Accounting and Finance, 2023)
In this paper, we provide a broad overview of the topics that are taught in undergraduate financial accounting and corporate finance classes. We document the overlaps in these introductory courses and describe the similarities and differences in how topics are taught in both disciplines. We then discuss, topic-by-topic, how instructors can reinforce the connections between the two fields in the classroom for more effective teaching and deeper learning. Our paper will help instructors to reinforce the connections between the two disciplines in the classroom for more effective teaching and deeper learning. It also provides the first step towards building effective teaching materials for accounting and finance courses for successful integration.